An innovative strategy harnessing self-activating CAR-NK cells to mitigate TGF-β1-driven immune suppression - Shin, Seung hun; Lee, Young Eun; Yoon, Han-Na; Yuk, Chae Min; An, Jun Yop; Seo, Minkoo; Yoon, Sangwon; Oh, Min-Suk; Shin, Sang Chul; Kim, Ji Hyung; Kim, Yong Jun; Kim, Jin-Chul; et al. (Pergamon Press Ltd., 2025)
The dysfunction of natural killer (NK) cells, mediated by transforming growth factor β1 (TGFβ1) within the tumor microenvironment, impedes antitumor therapy and contributes to poor clinical outcomes. Our study introduces self-activating chimeric antigen receptor (CAR)-NK cells that block TGFβ1 signaling by releasing a specifically designed peptide, P6, which targets mesothelin in pancreatic tumors. P6 originates from the interaction sites between TGFβ1 and TGFβ receptor 1 and effectively disrupts TGFβ1's inhibitory signaling in NK cells. Our analysis demonstrates that P6 treatment interrupts the SMAD2/3 pathway in NK cells, mitigating TGFβ1-mediated suppression of NK cell activity, thereby enhancing their metabolic function and cytotoxic response against pancreatic tumors. These CAR-NK cells exhibit potent antitumor capabilities, as evidenced in spheroid cultures with cancer-associated fibroblasts and in vivo mouse models. Our approach marks a substantial advancement in overcoming TGFβ1-mediated immune evasion, offering a promising avenue for revolutionizing cancer immunotherapy.